Performance and Haematological Indices of Broiler Chickens Fed Diet Containing Graded Level of Moist Heat Treated Gmelina arborea Seed Meal - Fatokhun, B O; Aguihe, P C; Olajide, B O; Aguihe, E O (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
Abstract. Experiment evaluating the effect of moist heat treated Gmelina arborea seed meal (MHGASM) on the growth performance and hematological indices in broiler chickens was conducted using one hundred and twenty (120) two weeks old broiler chickens which were randomly allotted to four dietary treatments consisting three replicates each with each replicate containing ten birds in a complete randomized design. The feed having 0% of MHGASM was taken as the reference diet, and the three diets to which MHGASM were included at graded level of 20, 25 and 30% as T2, T3 and T4 respectively were used for the comparison with the reference diet. Birds were fed the experimental diets and water supplied adlibitum during the feeding trial that lasted for 56 days. The results showed that final body weight, weight gain and feed conversion ratio were significantly affected by the dietary treatments while feed intake was not significantly influenced by the diets. Birds fed T4 (30% MHGASM inclusion level) diet had the highest final body weight, weight gain and best feed conversion ratio. Similarly, significant differences were recorded on all the hematological parameters investigated except hemoglobin concentration of the broilers across the treatment diets. Birds fed T4 diet recorded a higher mean values in all the hematological parameters except in WBC where T3 had the highest mean value. From the result of the study, it was therefore concluded that birds fed T4 (30% MHGASM)diet had an improved performance and the inclusion of moist heat treated Gmelina arborea seed in the diet of broilers do not have any negative effect on their physiological and immune system. Thus, moist heat treated Gmelina arborea seed meal may serve as a useful alternative for protein and fiber in compounding feed for broiler chickens. Key words: Performance, hematology, moist heat treated, Gmelina arborea, broiler chickens Abstrak. Percobaan mengevaluasi pengaruh tepung Gmelina arborea (jati) yang diuapkan (MHGASM) pada kinerja pertumbuhan dan indeks hematologis ayam broiler dilakukan menggunakan 120 ekor ayam broiler berumur 2 minggu yang secara acak dibagi ke dalam empat perlakuan pakan. Perlakuan diulang tiga kali, setiap ulangan terdiri atas 10 ayam, dan menggunakan Rancangan Acak Lengkap. Pakan dengan 0% MHGASM dijadikan pakan kontrol, dan tiga pakan mengandung MHGASM sebanyak 20, 25 dan 30% sebagai T2, T3 dan T4 digunakan sebagai pembanding pakan kontrol. Ayam mengkonsumsi pakan percobaan dan air diberikan ad libitum selama 56 hari percobaan. Hasil menunjukkan bahwa bobot akhir, penambahan bobot dan tingkat konversi pakan dipengaruhi oleh perlakuan pakan, sedangkan asupan pakan tidak dipengaruhi oleh pakan. Ayam yang diberi pakan T4 (30% MHGASM) memiliki bobot akhir dan penambahan bobot tertinggi, serta tingkat konversi pakan terbaik. Perbedaan nyata juga terdapat pada semua parameter hematologis kecuali konsentrasi hemoglobin pada broiler disetiap perlakuan pakan. Ayam yang diberi pakan T4 (30% MHGASM) memiliki nilai rataan tertinggi di semua parameter hematologi kecuali sel darah putih yang rataan tertingginya pada pakan T3 (25% MHGASM). Dari hasil penelitian disimpulkan bahwa ayam yang diberi pakan T4 menunjukkan peningkatan kinerja dan penambahan tepung jati yang diuapkan pada pakan broiler tidak menimbulkan dampak negatif terhadap fisiologi dan sistem kekebalan tubuh. Dengan demikian, tepung jati yang diuapkan dapat digunakan sebagai pengganti protein dan serat dalam pakan ayam broiler. Kata kunci: Kinerja, hematologi, penguapan, Gmelina arborea, ayam broiler